Origin, taxonomy and morphology of Vigna unguiculata (L.) Walp - Padulosi, S.; Ng, N.Q. (1997)
Cowpea (V. unguiculata) represents the main food legume in tropical Africa. Germplasm collecting missions launched over the past 10 years have provided genebanks with a wide array of variability within the cultivated and wild taxa of the species. Based on detailed studies on morphological diversity of live materials along with extensive survey of materials in major Vigna herbaria and ecogeographical information, a new intra specific classification recognizing 13 varieties of wild cowpea has been proposed and described. The study points out that the southernmost region of Africa is most probably the center of origin for the species V. unguiculata,while its domestication might have taken place in West Africa.